Partisipasi Wanita Penjual Kue Tradisional Dalam Meningkatkan Pendapatan Keluarga Menurut Perspektif Ekonomi Islam - Mulu, Beti (Institut Agama Islam Negeri Kendari, 2018)
This study aims to analyze: (1) Knowing the amount of women's income contribution to selling traditional cakes to family income, (2) Knowing the motivation of traditional cake-selling women; do the job of selling traditional processed foods doing the job of selling traditional cakes, and (3) To find out the participation of women traditional cake sellers in increasing family income according to the Islamic economic perspective. Data collection techniques were carried out in two ways, namely primary data through direct interviews using questionnaires to sample respondents and secondary data obtained from literature and literature compilation results. Data that had been collected was processed using qualitative and quantitative descriptive statistical analysis. The results of the study concluded that the amount of income of women selling traditional cakes is Rp. 7,200,000 or an average of Rp. 1,435,000, husband's income is Rp. 12,000,000 or an average of Rp. 2,400,000, while the income of other family members is Rp. 3,700,000 or an average of Rp. 740,000. From this description, it can be seen that the total income of the family of traditional cake-making women in Wawonggole Village, Unaaha District, Konawe Regency is Rp. 22,900,000 or an average of Rp. 4,275,000. Withthe contribution of women's business income, traditional cake sellers have a total family income of 31.44%. Motivation of female respondents or housewives to make and sell traditional cakes is to increase family income and to spend free time with positive activities. The participation of women traditional cake sellers in an effort to increase their family's income and help with economic needs is a good business and in line with Islamic shari'a because it is done with good effort and intention, as long as the wife does not violate the Shari'ah, namely not leaving her obligations in managing the house stairs to help her husband. in general, a woman's business as a traditional cake seller to help improve the family's economy may be done because it does not conflict with the principles of Islamic Economics.